The Foundations of Critical Studies in Education in Finland - Kosunen Sonja; Kauko Jaakko; Seppänen Piia; Thrupp Martin (Springer, 2025)
This chapter considers the historical roots of critical studies of Finnish education, particularly sociology, politics, and the history of education. It presents an interview with six emeriti professors who have participated in constructing the academic field. The chapter highlights their views about the greatest achievements of societally-oriented educational research in Finland, and what they considered the biggest disappointments or mistakes in this line of research.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling